Mathematical fixation: Search viewed through a cognitive lens. (2017) - Phillips, Steven; Takeda, Yuji
Abstract: We provide a mathematical category theory account of the size and location of the authors' Functional View Field (FVF). Category theory explains systematic cognitive ability via universal construction, that is, a necessary and sufficient condition for composition of cognitive processes. Similarly, FVF size and location is derived from a (universal) construction called a fibre (pullback) bundle.